2019
DOI: 10.1002/aoc.5154
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic characterization, biological screening and in vitro cytotoxic studies of 4‐methyl‐3‐thiosemicarbazone derived Schiff bases and their Co (II), Ni (II), Cu (II) and Zn (II) complexes

Abstract: A series of twenty compounds inclusive of bidentate Schiff bases derived from condensation of 4‐methyl‐3‐thiosemicarbazide with substituted derivatives of napthaldehyde/benzaldehyde/salicylaldehyde and their mononuclear Co (II), Ni (II), Cu (II) and Zn (II) complexes in molar ratio (1:1) were synthesized and characterized. The coordination behavior, modes of bonding and overall geometry of the compounds was known from the elemental analysis, spectral techniques (IR, UV–Vis, 1H NMR, 13C NMR, ESR and ESI‐mass), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 76 publications
(79 reference statements)
2
29
0
1
Order By: Relevance
“…In recent years, derivatives of thiosemicarbazones have demonstrated a broad range of biological and pharmacological activities (viz. antifungal, anticancer, antimicrobial, and antiviral) [32][33][34][35][36][37][38][39][40][41]. In line with this, we found no research on the in silico ADMET and drug-likeness prediction, as well as the anticancer activity of the same compound presented in our study.…”
Section: Introductionsupporting
confidence: 40%
“…In recent years, derivatives of thiosemicarbazones have demonstrated a broad range of biological and pharmacological activities (viz. antifungal, anticancer, antimicrobial, and antiviral) [32][33][34][35][36][37][38][39][40][41]. In line with this, we found no research on the in silico ADMET and drug-likeness prediction, as well as the anticancer activity of the same compound presented in our study.…”
Section: Introductionsupporting
confidence: 40%
“…Naphthaldehyde-based compounds have numerous presentations such as electrochemical, catalytic, photoluminescence, analytical, cytotoxic, antimicrobial and in vitro anticancer, antiproliferative, antioxidant, catechol's studies [33][34][35][36][37][38][39][40][41][42][43] Transition metal compounds play important role in bio-inorganic chemistry and redox enzyme systems [44]. Copper is one of the most important elements in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simple synthesis method, coordination variety, catalytic, medicinal and biological applications Schiff base ligands and their metal complexes achieved much attention [6]. Many of the Schiff base metal complexes act as antifungal, antibacterial [7], antiviral [8], herbicidal [9], analgesic [10], anti-inflammation [11,12], antioxidant [6,13], antitumor [14,15], anticancer [16,17], antitubercular [18][19][20] agent. Previously, many investigations have been demonstrated that, Schiff base with aromatic and hetarocyclic ring coordinated with transitional metals show potential activity against MTB and different microorganisms [18,[20][21][22][23][24], suggesting new possible candidate to break the resistant of MTB.…”
Section: Introductionmentioning
confidence: 99%